2006
DOI: 10.1139/f06-052
|View full text |Cite
|
Sign up to set email alerts
|

Does eel metamorphosis cause a breakdown in the tenets of otolith applications? A case study using the speckled worm eel (Myrophis punctatus, Ophichthidae)

Abstract: Several basic tenets of otolith research have been questioned recently with regard to eel metamorphosis. Specifically, some researchers have suggested that otolith increment formation is not daily, and otolith material may be resorped during metamorphosis. We conducted a rearing experiment to test the hypothesis that increment formation is daily and that the otolith continues to grow during eel metamorphosis. We marked the otoliths of wild-caught Myrophis punctatus leptocephali and reared these fish through me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Species collected in the mostly warm Indo-Pacific region have growth rates <1 mm/d and linear relationships between age and body length, with growth slowing down as maximum size is reached ( Table 1; . These relationships and the finding of apparent lunar cycles of spawning based on backcalculated hatching dates (Ishikawa et al 2001;Tsukamoto et al 2003;Lee et al 2008), suggest that increments are deposited daily in these species (Powles et al 2006).…”
Section: -2 Leptocephalus Growthmentioning
confidence: 89%
See 2 more Smart Citations
“…Species collected in the mostly warm Indo-Pacific region have growth rates <1 mm/d and linear relationships between age and body length, with growth slowing down as maximum size is reached ( Table 1; . These relationships and the finding of apparent lunar cycles of spawning based on backcalculated hatching dates (Ishikawa et al 2001;Tsukamoto et al 2003;Lee et al 2008), suggest that increments are deposited daily in these species (Powles et al 2006).…”
Section: -2 Leptocephalus Growthmentioning
confidence: 89%
“…An increase in increment width during metamorphosis was also found in tarpon leptocephali held in the laboratory (Shiao and Hwang 2006;Chen et al 2008). Powles et al (2006) showed that otoliths of ophichthid leptocephali, Myrophis punctatus, continued to deposit increments during metamorphosis, but they did not analyze increment widths. No increase in increment widths were observed in anguillid glass eels that recruited to Iceland however, which may have been due to the cold temperatures and slow metamorphosis experienced by those individuals during their leptocephalus stage (Kuroki et al 2008b).…”
Section: Aqua-bioscience Monographs Vol 2 No 4 2009mentioning
confidence: 95%
See 1 more Smart Citation
“…Cieri and McCleave (2000) proposed that there may be no otolith deposition during metamorphosis in the Atlantic eels, but no heavy check was observed near the otolith increments corresponding to metamorphosis in the Icelandic glass eels examined here. In addition, recent studies on other elopomorph fishes have shown that otolith daily deposition continues through metamorphosis in leptocephali held in the laboratory as they transformed into the glass eel or juvenile stage (Chen and Tzeng 2006;Powles et al 2006). This suggests that if there is a possible period of lack of otolith deposition in the otoliths of some Atlantic glass eels, it is probably not during metamorphosis, but is more likely when the glass eels have reached their recruitment areas and stay on the bottom without feeding or actively migrating inshore.…”
Section: Estimated Hatching Datementioning
confidence: 99%
“…The tank was suspended in the larger maintenance tank to avoid temperature shock on 7 December 2002, for 12 h, to place a dye mark in the otoliths, as in Tsukamoto (1988). We could then follow subsequent growth and increment number past this mark (as in Powles et al 2006). After 12 h, survivors were replaced in their holding tank.…”
Section: Age Validationmentioning
confidence: 99%